A novel parallel overlapping mode for complete ablation of large benign thyroid nodules in a single-session radiofrequency ablation - Wu, Tao; Zheng, Bowen; Tan, Lei; Yin, Tinghui; Lian, Yufan; Xu, Shicheng; Ye, Jin; Ren, Jie (Frontiers in Endocrinology, 2022)
Background: Radiofrequency ablation (RFA) has been widely applied in patients with benign thyroid nodules (BTNs), and complete ablation in a single-session treatment brings great benefits to patients. While how the ablation should be planned and performed to achieve complete ablation in a single-session treatment in large BTNs remains unknown. Purpose: To determine a more suitable ablation strategy for sufficient treatment in a single-session treatment. Materials and Methods: This retrospective study included 108 BTNs receiving RFA treatment. These patients were divided into two groups: group A using one insertion point with a fan-shaped overlapping mode and group B using multiple insertion points with a novel parallel overlapping mode. All the treatments used a hydrodissection approach and moving-shot technique. Contrast-enhanced ultrasonography (CEUS) was used to guide the supplementary ablation. Follow-ups were performed at 1, 3, 6 and 12 months. The rates of supplementary ablation, the rates of complete ablation, complication and treatment effects between the two groups were compared. Results: The group B had larger treated nodules (14.4ml vs 8.5 ml, P=0.008) than group A, while group B had a lower rate of supplementary ablation (21.6% vs 75.4%, P<0.001), especially in the BTNs with craniocaudal diameters ≥30mm (22.0% vs 100%, P<0.001). With the assistance of supplementary ablation, both groups achieved similar rates of complete ablation (94.7% vs 94.1%, P=0.480). Two groups showed similar VRRs at 12-month follow-up (77.9% vs 77.5%, P=0.894) and similar rates of complications (3.5% vs 2.0%, P=1.000). Conclusions: Needle placement using the multiple insertion points with a novel parallel overlapping mode would be easier to achieve complete ablation with less supplementary ablation, especially in large nodules.